Innovation as a Tool to Improve Public Service Delivery: South African Government Perspective - Thusi, Xolani; Mahlatse, Ragolane; Matyana, Mandisi (Universitas Jember, 2023)
South African citizens are still facing problems of poor service provision in the local, provincial, and national governments after 28 years of democracy. The standard of public service provision and implementation in South Africa is deteriorating. It is important to note that due to the country's high level of unemployment, the majority of South African citizens rely on government service provision. Because of the government's inability to reach every citizen with efficient and effective service provision, South Africa has the highest level of inequality and a huge gap between the rich and the poor, making efficient service provision a solution to bridge the gap and inequality. This article proposed that the government must develop techniques to boost innovation in the public sector to prioritize service delivery in the country, as there are many challenges surrounding the South African public sector. Qualitative approach was adopted in this research, through the review of recent secondary sources to address the objectives of this study.Keywords: Citizens, Government, Innovation, Service Provision.